The complete poems of Michelangelo : Joseph Tusiani's classic translation - Michelangelo Buonarroti, 1475-1564 (Lorenzo da Ponte Italian library., 2023)
"Though known primarily as a sculptor and painter, Michelangelo was also a poet. In his lifetime, Michelangelo wrote over 300 poems, many of which were works of devotion and love poems of a spiritual and mystical nature. In 1961, Joseph Tusiani offered the first English translations of the complete corpus of Michelangelo's poems. These translations illuminated the subtleties of both the source and target language, giving Michelangelo's verse a freshness, a depth, and an inventiveness that time has not been able to obscure. The Complete Poems of Michelangelo reproduces Tusiani's masterful translation. In addition to Tusiani's introduction and translations, this new edition contains Michelangelo's original Italian poetry, a chronology of his life and works, a biographical profile of Tusiani, and an interview with Tusiani exploring his musings on classic literature and the subtle art of translation. The Complete Poems of Michelangelo sheds light on Tusiani's many exceptional accomplishments during his long and prolific life as a scholar, poet, translator, and artist."--